Synergistic mechanisms of steel slag, granulated blast furnace slag, and desulfurization gypsum in high-content steel slag-based cementitious backfill materials - Jianshuai Hao; Zihan Zhou; Zhonghui Chen; Yanjun Shen; Kuizhen Fang; Fei Tang; Fengyang Xin; Lingfei Zhang (International Journal of Mining Science and Technology)
In the steel slag-based mine backfill cementitious material systems, the hydration reaction mechanisms and synergistic effects of steel slag (SS), granulated blast furnace slag (GBFS), and desulfurization gypsum (DG) are crucial for performance optimization and regulation. However, existing studies have yet to fully reveal the underlying synergistic mechanisms, which limits the application and promotion of high SS content in mine backfill and low-carbon building materials. This study systematically explores the synergistic effects between various solid wastes and their regulation of the hydration process in the SS-based cementitious system through multi-scale characterization techniques. The results show that GBFS, by releasing active Si4+ and Al3+, triggers a synergistic activation effect with Ca2+ provided by SS, promoting the formation of C-S-H gel and ettringite, significantly optimizing the hardened paste microstructure. When the GBFS content reaches 30%, the C-S-H content increases by 40.8%, the pore size distribution improves, the proportion of large pores decreases by 68.7%, and the 90-day compressive strength increases to 5 times that of the baseline group. The sulfate activation effect of DG accelerates the hydration of silicate minerals, but excessive incorporation (>16%) can lead to microcracks caused by the expansion of AFt crystals, resulting in a strength reduction. Under the synergistic effect of 8% DG and 30% GBFS, the hydration reaction is most intense, with the peak heat release rate reaching 0.92 mW/g and the cumulative heat release amount being 240 J/g. By constructing a “SS-GBFS-DG-cement” quaternary synergistic system (mass ratio range: SS:GBFS:cement:DG=(50–62):(20–40):10:(8–12)), the matching of active components in high-content SS systems was optimized, significantly improving microstructural defects and meeting engineering application requirements. This study provides a theoretical basis for the component design and performance regulation of high-content SS-based cementitious materials.